The three-body problem from Pythagoras to Hawking. (2016) - Valtonen, M. J (Mauri J.), 1945-; Anosova, Joanna; Kholshevnikov, Konstantin; Mylläri, Aleksandr; Orlov, Victor; Tanikawa, Kiyotaka
No abstract available